Note sur l’Étude paléopathologique des individus inhumés dans l’ancien monastère des prêtres Lóios de Arraiolos (Portugal) - Paula Tavares (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The old monastery of the Lóios de Arraiolos priests (Alto Alentejo, Portugal) dedicated in the past to «Nossa Senhora da Assunção», was inhabited between the 16th and 19th century by the blue canons, also called the Lóios priests. The excavation of the north, west and east wings of the cloister, carried out in 1994 and 1995, produced many copper and gold objects, as well as human skeletons in anatomical connexion and “ossuaries”. The present study concerns the macroscopic and radiological examination of 17 skeletons from the north and west wings, as well as the “ossuaries” present in three of these burials. Of the individual skeletons in connexion studied, nine are immature (five of them died in the perinatal period or before the age of seven/eight years, four are adolescents) and eight are adults (four men, two women and two of indeterminate sex).The palaeopathological analysis of the teeth indicates a low frequency of caries, heavy tooth wear, and the formation of tartar. Cases of periodontal disease and one case of abscess in the jaw were observed. Some cases of arthritis, Schmorl´s nodules, cribra orbitalia, porotic hyperostosis, among other pathologies, are also present in this material. The differential diagnosis carried out for the infections of the periosteum in the long bones and on the internal surface of the ribs as well as a case of hypervascularisation in the vertebrae led to a diagnosis of tuberculosis. The high frequency of periostitis on the tibiae and fibulae is interpreted taking into account the physical activity and other known cultural data for this population. The results obtained are discussed according to the archaeological context, the states of preservation and the data relative to the way of life of this population.